2018
DOI: 10.13189/cea.2018.060304
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Concrete with Glass Powder as Partial Replacement of Cement

Abstract: The effects of partially replacing of cement with glass powder in concrete were studied and therefore found that some extent could be replaced which contributes in strength development. Cement was partially replaced with glass powder at varying percentages such as 10%, 20% and 30% and several concrete cylinders were casted along with plain concrete specimen. The cylinders were tested for compressive strength and split tensile strength at the age of 7, 14 and 28 days and were compared with the results of plain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…Effects of the use of waste glass as cement replacement on some mechanical properties such as CS, STS, and FS have been investigated. In this part of the study, values of CS, STS, and FS for plain concrete and concrete produced from different glass powder amounts have been collected from the research publications [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ]. Then, measured strength values of concrete produced with waste glass were first normalized by plain concrete strengths.…”
Section: Resultsmentioning
confidence: 99%
“…Effects of the use of waste glass as cement replacement on some mechanical properties such as CS, STS, and FS have been investigated. In this part of the study, values of CS, STS, and FS for plain concrete and concrete produced from different glass powder amounts have been collected from the research publications [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ]. Then, measured strength values of concrete produced with waste glass were first normalized by plain concrete strengths.…”
Section: Resultsmentioning
confidence: 99%
“…The improvement in splitting tensile strength can be associated with the pozzolanic reaction and filling ability of SF [13]. The filling ability of the small particles of the SF can reduce the negative effect of the micro-cracks on the RCA; resulting in better splitting tensile strength for the RAC [22][23][24][25].…”
Section: Results Of Splitting Tensile Strengthmentioning
confidence: 99%
“…In addition, Zakir et al (2016) showed that the tensile strength by splitting of glass powder concrete increases by about 29% at 28 days. Rahman and Uddin (2018) and Mwizerwa and Garg (2017) found an increase in tensile strength by splitting of 3.04% and 51.16%, respectively, in 30% replacement of cement by glass powder. Figure 4 illustrates the results of the effect of glass powder on the tensile strength for various works.…”
Section: Introductionmentioning
confidence: 95%
“…Kumar and Sood (2017) found that cement can be replaced by glass powder by up to 20% without any loss of flexural and tensile strength in all concrete variants studied. Rahman and Uddin (2018) concluded that 30% of cement replacement achieves maximum tensile strength by splitting compared to the control concrete at 28 days. Olofinnade et al (2017) showed that it is possible to produce medium-strength durable concrete for structural applications using 20% glass powder as a cement replacement.…”
Section: Introductionmentioning
confidence: 99%